Management indicators (KPIs) and (OKRs) as managerial tools in colombian business development - López López, Mildred Karola; Medina Acero, Cesar Augusto; Cortés Cortés, Jorge Mario (Cuadernos de Administración, 2025)
This article reflects on the use of Key Performance Indicators (KPIs) and Objectives and Key Results (OKRs) as key managerial tools in the development of Colombian businesses. Through a documentary analysis that included the review of approximately 30 articles sourced from Semantic Scholar, WOS, Scopus, and other specialized platforms, the implementation of these tools was assessed across sectors such as technology, manufacturing, and finance. The study applied exclusion criteria to ensure contextual relevance and covered both academic research and institutional publications. The methodology employed thematic coding to identify patterns and challenges in the adoption of KPIs and OKRs.The results indicate that while KPIs are used by 30-40% of companies, primarily to improve operational efficiency and transparency, the implementation of OKRs, adopted by 15-20% of companies, is more recent and linked to emerging sectors like tech startups. The main conclusions highlight that these tools have promoted resource optimization, better strategic alignment, and greater adaptability in a dynamic market environment. However, barriers remain, such as a lack of training and resistance to change in Small and Medium-sized Enterprises (SMEs). The study suggests that the proper adoption of KPIs and OKRs could be key to driving competitiveness and innovation within the Colombian context.